2020
DOI: 10.1001/jamapediatrics.2019.4488
|View full text |Cite
|
Sign up to set email alerts
|

Association of Trajectory and Covariates of Children’s Screen Media Time

Abstract: IMPORTANCE Many children begin interacting with screen media as early as infancy. Although screen time is associated with negative developmental consequences, few longitudinal studies in the United States have examined covariates of screen time among children under 3 years of age. OBJECTIVES To identify trajectories of screen time among children aged 1 to 3 years, to examine their association with screen use at 8 years of age, and to assess potential determinants of screen time. DESIGN, SETTING, AND PARTICIPAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 51 publications
9
39
0
2
Order By: Relevance
“…These family stressors may also contribute to OWOB among children on Guam. With respect to OWOB prevention guidance, the study found evidence supporting previous studies' findings that traditional or low acculturation to be protective against obesity [39,59,60]. Healthy cultural behaviors, both unique to and shared across ethnic group(s), should be incorporated in future obesity interventions by highlighting healthy cultural values, practices and traditional foods.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These family stressors may also contribute to OWOB among children on Guam. With respect to OWOB prevention guidance, the study found evidence supporting previous studies' findings that traditional or low acculturation to be protective against obesity [39,59,60]. Healthy cultural behaviors, both unique to and shared across ethnic group(s), should be incorporated in future obesity interventions by highlighting healthy cultural values, practices and traditional foods.…”
Section: Discussionsupporting
confidence: 72%
“…The proportion of children exceeding screen-time recommendation in this study (83%) was comparable to the 87% reported among a prospective birth cohort of children born in New York led by researchers from the NIH Eunice Kennedy Shriver National Institute of Child Health and Human Development [60]; however, the birth cohort included children below two years of age, which is an age group not represented in the Guam study. Additionally, while screen-time increased with preschool age in the birth cohort, the total hours decreased to below the recommended two hours by 7-8 years old possibly due to school activities [60].…”
Section: Discussionsupporting
confidence: 71%
“…In previous studies, conflicting results were reported about the relationship between maternal education, paternal education, gender of the child, and screen time. 26,27 Similar to Trinh and his colleagues, 28 the present study demonstrated an inverse relationship between parental education level and screen time of children and also found that male gender was associated with increased screen time. In addition, Maatta et al, 29 showed that parents with high education have lower descriptive norms, use fewer screens in front of children, and place greater importance on limiting children's screen time compared to parents with low education.…”
Section: Di̇scussi̇onsupporting
confidence: 88%
“…Findings related to maternal occupation, presence of siblings and the child's screen time differed in past studies. 28 Hinkley et al, 30 identified no association between maternal employment, the presence of siblings, and screen time for preschool children. On the contrary, Wu et al, 31 reported that screening devices were used more frequently in children whose mothers were housewives compared to working mothers.…”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…Exploratory subgroup analyses revealed a small but significant effect in reducing BMI in interventions in which a screen time component was present (g = 0.23, 95% CI = 0.10-0.36) versus absent (g = 0.05, 95% CI = -0.02 to 0.12) relative to the control or comparison group [Q B (1) = 11.24, p = <0.001]. This is an important finding given that screen time habits in children younger than the age of three are associated with increased screen use at 8 years of age, 67 and the robustness of research showing that screen time exposure is associated with an increased risk of obesity. 68 This also highlights the critical role of parents in reducing childhood obesity, 69 and the need to identify specific strategies and provide skills-training to support parents of preschoolers who often find it challenging to limit screen time exposure 70 These findings are consistent with the Community Preventive Services Task Force, which found strong evidence supporting the efficacy of interventions addressing screen time reduction to promote healthy weight in children aged 13 and younger.…”
Section: Childhood Obesity September 2020mentioning
confidence: 71%